Tanzanian Women in Their Own Words: Stories of Disability and Illness - Feinstein, Sheryl; D'Errico, Nicole C. (Lexington Books, 2009)
Tanzanian Women in Their Own Words is a compilation of oral histories by Tanzanian women living with disabilities or chronic illnesses. Beginning with their earliest childhood memories, the narrators weave their life stories through adulthood, telling of the hardships and support systems in their daily lives. A rich knowledge of Tanzanian culture is embedded in each story; for instance the pivotal role tribal affiliation, polygamy, and poverty play in society is addressed. HIV/AIDS, cancer, polio, female circumcision, and TB are just a few of the health issues covered; Feinstein and D'Errico make a concerted effort to include the major medical challenges facing this developing country, including an interview with an albino woman that introduces the little discussed atrocity of albinos being murdered for body parts to be used in ritual medicine practices. In spite of the abuse and exclusion many of the women suffer, eventually each learns to live in harmony with her reality. This makes their lives inspiring and gives perspective to those facing physical challenges. Tanzanian Women in Their Own Words encourages readers to consider issues of health care, transportation, ignorance, polygamy, gender discrimination, and rural isolation. Through learning about the health challenges faced by Tanzanian women, students are introduced to the lifeways and concerns of Tanzanian culture, the challenges faced by many developing countries, and the intimate and evocative level of detail that can only be discovered through intensive ethnographic fieldwork.